Trade Integration Indonesia-ASEAN4 in AEC Era: A Case of Wood-based Products - Pauline Henriette Pattyranie Tan (The Winners, 2020)
The research was conducted to find out the level integration intensity using Grubel-Lloyd index. Moreover, since Horizontal and Vertical Intra-Industry Trade (IIT) could be distinguished, it was important to find out whether Indonesia-ASEAN4 IIT of wood-based products was in one of these categories. The Hufbauer index had been used as the measurement of product differentiation. Therefore, it could be the basic information for taking policy to boost Indonesia-ASEAN IIT for this industry. The data used comprise annual statistics of wood-based product export and import between Indonesia and ASEAN4 from 2010 to 2016 which were divided into eight categories of five digits ISIC. The Grubel-Lloyd index result shows that only ISIC 16102 has achieved strong integration, the others are still in mild and even weak integration. The Hufbauer index results show that all the values approached to zero, indicated that overall wood-based products traded by Indonesia-ASEAN4 are horizontally differentiated.